The Importance Of Taekwondo Training In The Physical Development Of 7-8 Year Old Children - Nozima Erkinova (Zien Journals, 2025)
This article discusses the issues and problems of taekwondo practitioners' physical and mental training to fully reveal their individual abilities and potential, which are hidden even in a person.
Keywords: physical; training; individual ability